Identification of Mean Years of Schooling as a Control for RPJMD: A Spatial Autocorrelation Approach - Harun Al Azies; Anwar Efendi Nasution (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This article will identify the mean years of schooling in East Java as a control for achieving RPJMD. Inequality in the development of education leads to inequalities between the regions of East Java. This is due to the different regional characteristics, it is, therefore, necessary to respond to it by carrying out a regional mapping based on the education indicators listed in the RPJMD of each region using a statistical analysis approach, namely spatial autocorrelation. The variable that becomes the indicator in this study is the Mean Years of Schooling (MYS), the unit of observation being the regencies/cities of East Java. The results of the research that has been conducted can be concluded that the mean years of schooling for the population of East Java Province is seven years where urban areas have a better average length of schooling than in districts, and there are only nine areas in East Java that have MYS exceeding the RPJMD target. In the Global Moran's I test, there is a positive autocorrelation or cluster pattern that exhibits similar characteristics in adjacent locations, and the results of the local Morans’ show that there are nine regions that have spatial relationships with their most significant areas relatives based on the MYS indicator. These areas are Bondowoso Regency, Bangkalan Regency, Pamekasan Regency, Gresik Regency, Jember Regency, Probolinggo Regency, Sampang Regency, Sidoarjo Regency and Surabaya City